2017
DOI: 10.1111/jai.13266
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the molecular diversity of Eleotridae (Gobiiformes) using mitochondrial DNA

Abstract: Summary Species with wide geographic distributions can consist of different lineages or even of different species. The present study evaluated the molecular diversity of the family Eleotridae by analyzing sequences of the COI gene from species collected in different locations in a Neotropical region as well as sequences from BOLD and GenBank. The analysis revealed the distinction and differentiation of a variety of species with high statistical support, including Gobiomorus dormitor (two lineages), Dormitator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Furthermore, and in agreement with the latter, a recent barcoding study with a broader geographical and taxonomical sampling within the Eleotridae, pointed to the Eastern Pacific species G. polylepis as the sister of G. dormitor , and H. latifasciata as sister to the two of them (Guimarães-Costa et al. 2017 ). According to this, G. dormitor and G. polylepis would constitute the geminate species pair in the genus Gobiomorus .…”
Section: Resultssupporting
confidence: 69%
“…Furthermore, and in agreement with the latter, a recent barcoding study with a broader geographical and taxonomical sampling within the Eleotridae, pointed to the Eastern Pacific species G. polylepis as the sister of G. dormitor , and H. latifasciata as sister to the two of them (Guimarães-Costa et al. 2017 ). According to this, G. dormitor and G. polylepis would constitute the geminate species pair in the genus Gobiomorus .…”
Section: Resultssupporting
confidence: 69%
“…2230 ). The DNA barcoding approach has permitted considerable advances in the understanding of fish diversity, in particular, the elucidation of taxa with similar traits 3140 . In the present study, the composition of the fish fauna of the Parnaíba Delta was diagnosed by DNA Barcoding, providing new insights into the local fish diversity in this important coastal complex, while also expanding the global barcoding database.…”
Section: Introductionmentioning
confidence: 99%
“…Phylogeographic studies of several diadromous fishes in Middle America have also demonstrated population‐level divergence between the Caribbean and Gulf of Mexico ( Dajaus monticola , McMahan et al ., 2013; Dormitator maculatus (Bloch, 1792), Galván‐Quesada et al ., 2016; Gobiomorus dormitor Lacepède, 1800; Guimarães‐Costa et al ., 2017). Awaous banana similarly exhibits this biogeographic pattern, with 1.86% COI divergence between these two clades ( i.e ., Caribbean and Gulf of Mexico).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to stenohaline or euryhaline fishes, diadromous fishes can exhibit interesting patterns of evolutionary history and population structure given their occupancy of both freshwater and marine systems as integral parts of their life histories. These structured biogeographic patterns have been observed in several diadromous taxa in Middle America, including sleepers (family Eleotridae, Guimarães‐Costa et al ., 2017 and Galván‐Quesada et al ., 2016) and mullets (family Mugilidae, Díaz‐Murillo et al ., 2017 and McMahan et al ., 2013). Intraspecific divergence was recovered across all of these taxa, with different lineages present in Atlantic and Pacific‐slope rivers, as well as multiple lineages within each slope.…”
Section: Introductionmentioning
confidence: 95%